Handbook of quality assurance for university teaching - Ellis, Roger, 1937-; Hogard, Elaine (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2019)
'This practical and authoritative handbook provides a comprehensive overview of the issues and approaches to assuring quality in university teaching. Including contributions from major international figures, the book contains a wealth of ideas and practical advice to help universities commit to quality in teaching and offers insights into how the topics raised can be directly applied. The book initially identifies some of the key issues surrounding the topic, such as the evidence-based identification of teaching quality; the training of university lecturers and faculty; external and internal quality assurance; the tension between professional autonomy and governmental regulation; and the involvement of students in developing quality. It then moves on to present ideas and initiatives to address these problems, tackling the subject through four sections: - Assuring Quality - questioning what quality assurance means and how it might be practised; - Identifying Quality - examining what knowledge exists at present and how it might be further researched; - Developing Quality - investigating the development of staff through teacher training and appraisal; - Case Studies of Quality Assurance - reviewing six case studies of quality assurance in a range of contrasting subjects including the professional subjects of Medicine, Nursing and Teacher Training which are also addressed systemically in the first section. Full of practical advice, Handbook of Quality Assurance for University Teaching is an invaluable and unique resource for Faculty, Subject Leaders, University Administrators and Quality Assessors'--
Quality assurance for university teaching: issues and approaches -- The quality assurance agency -- Learning and teaching developments across UK higher education -- A British standard for university teaching? -- University teaching: a professional model -- Programme evaluation: a key to assuring quality in higher education -- Institutional research and quality assurance -- The power of proxies: an examination of performance management frameworks -- Quality assurance in medical education: accreditation and teaching standards in Australia, USA and Canada, and UK -- Quality assurance and enhancement in nurse education -- Quality assurance and accountability in initial teacher education in England -- The quality assurance of higher education from the perspective of professional, statutory, and regulatory bodies -- Quality assurance through national assessments -- How can students engage in assuring quality of university teaching? -- Assuring quality through student evaluation from paper to cloud-based by Maurice -- The student role in quality: from data source to partner and back again -- Quality assurance in healthcare and the implications for university teaching -- Assessing teaching quality in Hungary -- Effective teaching? -- Teaching styles of award winning professors -- Identifying quality in teaching using consultative methods -- Student engagement with and perceptions of quality and standards -- Beyond satisfaction: student voice, student engagement and quality learning -- Beyond student ratings : 14 other sources of evidence to evaluate teaching -- Developing a higher education standards framework -- Staff development and quality assurance -- Case study: reflections from a centre for academic development in a shifting context -- Appraisal schemes and their contribution to quality in teaching -- Developing teaching standards: a professional development perspective -- Private coaching for university teachers: external help to find the right balance of power and responsibility -- Quality assurance in medical education: harmonizing external and internal demands for change -- Quality assurance in nurse education: professional and academic perspectives -- Experience of an OFSTED inspection of an initial teacher education partnership -- Teaching quality in art, design and medicine: tacit knowledge and experience -- Performing, composing, reflecting and researching: recognising and managing quality in undergraduate music programmes -- Professional regulation, research training and the development of peer mentorship in UK psychology programmes.
Includes bibliographical references and index.
Keywords: College teaching -- Evaluation